A novel service level agreement model using blockchain and smart contract for cloud manufacturing in industry 4.0. Issue 12 (2nd December 2022) - Tan, Wenan; Zhu, Hai; Tan, Jinjing; Zhao, Yao; Xu, Li Da; Guo, Kai
ABSTRACT: The number of service offerings in cloud manufacturing continues to grow, so that service level agreement (SLA) within cloud manufacturing is increasingly used to ensure the coordination of the cross-organisational business processes between the cloud service providers (CSP) and cloud service consumers (CSC). The definition of SLA and monitoring SLA's performance are significant and should be highly valued to ensure the effectiveness and efficiency of business services. At present, the third-party monitoring methods based on service credit are mainly applied in cloud manufacturing environments. There is no effective supervision mechanism to monitor the third party and no efficient punishment mechanism on SLA violation. To address aforementioned issues, this paper proposes a novel Service Level Agreement model by integrating Blockchain and Smart Contract (SLABSC), in which trust issues among CSP, CSC, and the third-party monitoring can be addressed through Blockchain technologies. The method proposed in this paper realises the full functionality of SLABSC and facilitates data security, and it can be used to supervise CSP to provide better services. Experiments results show that the performance of the proposed model is valid and efficient.